Physicochemical properties of microwave heated sago (Metroxylon sagu) starch - Zailani, Mohd Alhafiizh; Abd Razak, Hanisah Kamilah; Awang Husaini‬, ‪Awang Ahmad Sallehin; Sarbini, Shahrul Razid (Taylor & Francis, 2021)
Sago starch is an underutilized starch due to its low functionality in food formulation. Modification is effective in improving starch functional properties. In this study, the starch were modified to enhance its functional properties. The starch was microwave-heated with different treatment durations of 5, 10, 15, or 20 min, separately, yielding microwave-heated starches (MHT1, MHT2, MHT3, and MHT4). The modified starches have irregular shaped granules and fissures while maintaining their mean diameters. The degree of double helix had increased, indicating more double helix structure of amylose formed. The modified starches’ moisture content, solubility, and paste clarity were significantly decreased. The MHT4 had its swelling power and syneresis increase. In conclusion, the treatment duration influenced the physicochemical properties of the sago starch, which is related to the formation of amylose double helix structure. Further study should focus on the formation of double helix structure in starch and its impact towards food structure.